Tren Global Penelitian Kompetensi Digital di Institusi Pendidikan: Studi Analisis Bibliometrik - Farid Fauzi (ALSYS, 2026)
Digital competence is an important 21st-century competence that supports digital transformation in education and various other sectors. The increasing number of scholarly publications on digital competence indicates the need for a comprehensive mapping of research developments to understand the direction, focus, and opportunities for future studies. This study aims to analyze global publication trends, the development of research themes, and to identify the main focus and research opportunities concerning digital competence in educational institutions. This study used a bibliometric approach to 160 articles indexed in Scopus during the 2016–2025 period. The analysis was conducted using Bibliometrix and VOSviewer to map publication trends, citations, keyword occurrence, co-occurrence networks, and the evolution of research themes. The findings show that publications on digital competence have increased, especially since 2021, and reached their peak in 2025. The research themes are dominated by digital literacy, ICT, and professional development, while emerging themes such as artificial intelligence, digital transformation, online learning, and professionalism in digital competence have begun to develop in recent years. These findings indicate a shift in research focus from digital literacy toward the integration of intelligent technologies and the development of professional digital competence. The conclusion of this study affirms that research on digital competence in educational institutions continues to develop dynamically and contributes to expanding understanding of digital transformation in education. The implications of this study provide a conceptual basis for researchers, educators, and policymakers in formulating research agendas and strategies for strengthening digital competence that are relevant to the needs of contemporary education.